Sex differences and age-related changes in vertebral body volume and volumetric bone mineral density at the thoracolumbar spine using opportunistic QCT - Rühling, Sebastian; Dittmann, Jonas; Müller, Tobias; Husseini, Malek El; Bodden, Jannis; Hernandez Petzsche, Moritz R.; Löffler, Maximilian T.; Sollmann, Nico; Baum, Thomas; Seifert-Klauss, Vanadin; Wostrack, Maria; Zimmer, Claus; et al. (Frontiers in Endocrinology, 2024)
Objectives: To quantitatively investigate the age-and sex-related longitudinal changes in trabecular volumetric bone mineral density (vBMD) and vertebral body volume at the thoracolumbar spine in adults. Methods: We retrospectively included 168 adults (mean age 58.7±9.8 years, 51 women) who received ≥7 MDCT scans over a period of ≥6.5 years (mean follow-up 9.0±2.1 years) for clinical reasons. Level-wise vBMD and vertebral body volume was extracted from 22720 thoracolumbar vertebrae using a convolutional neural network (CNN)-based framework with asynchronous calibration and correction of the contrast media phase. Human readers conducted semiquantitative assessment of fracture status and bony degenerations. Results: In the 40-60 years age group, women had a significantly higher trabecular vBMD than men at all thoracolumbar levels (p<0.05 to p<0.001). Conversely, men, on average, had larger vertebrae with lower vBMD. This sex difference in vBMD did not persist in the 60-80 years age group. While the lumbar (T12-L5) vBMD slopes in women only showed a nonsignificant trend of accelerated decline with age, vertebrae T1-11 displayed a distinct pattern, with women demonstrating a significantly accelerated decline compared to men (p<0.01 to p<0.0001). Between baseline and last follow-up examinations, the vertebral body volume slightly increased in women (T1-12: 1.1±1.0 cm 3 ; L1-5: 1.0±1.4 cm 3 ) and men (T1-12: 1.2±1.3 cm 3 ; L1-5: 1.5±1.6 cm 3 ). After excluding vertebrae with bony degenerations, the residual increase was only small in women (T1-12: 0.6±0.6 cm 3 ; L1-5: 0.7±0.7 cm 3 ) and men (T1-12: 0.7±0.6 cm 3 ; L1-5: 1.2±0.8 cm 3 ). In non-degenerated vertebrae, the mean change in volume was <5% of the respective vertebral body volumes. Conclusion: Sex differences in thoracolumbar vBMD were apparent before menopause, and disappeared after menopause, likely attributable to an accelerated and more profound vBMD decline in women at the thoracic spine. In patients without advanced spine degeneration, the overall volumetric changes in the vertebral body appeared subtle.